Public expenditure and growth: a decomposed expenditure analysis for states in India - Jena, Pratap Ranjan (2004)
The paper attempts to study the relationship between government expenditure and growth parameter across states in India at a decomposed level, as the direction of relationship at aggregate level may not be very convincing. Time series property of state expenditure data has been examined to account for non-stationary character of macro-economic series and impact of expenditure variables on growth of real GSDP has been examined in a panel regression model. The results emphasise that state spending on infrastructure, productive sectors, and investment in physical and human resources has positive impact on growth parameter. It is further concluded that states should aim at reducing unproductive expenditure and rationalise the expenditure pattern to augment process of growth. - Reproduced.
Keywords: Public expenditure - India; Public expenditure